Examination of hearing loss among school-aged children in Greenland. (October 2021) - Jensen, Jakob Schmidt; Schnohr, Christina; Skovsen, Cecilie Friis; Homøe, Preben; Jensen, Ramon Gordon
Abstract: Background: The highest prevalence of chronic suppurative otitis media is seen among children in Greenland. The purpose of this study was to investigate the prevalence of hearing loss among school children in Sisimiut, the second-largest city in Greenland. Material and method: All 423 children from 5th to 10th grade from the two schools in Sisimiut and the nearby settlements were invited to participate. Participants filled out a questionnaire at home with their parents before ear-examination and audiometry. Risk factors for hearing loss and otitis media (OM) related otoscopy findings were analyzed by binomial logistic regression. Results: A total of 185 children between 9 and 15 years of age (median: 11 years, IQR: 10–13) were included; 60% (n = 111) were girls. Fifty-four children (29%) were found to have hearing impairment using a PTA of 15 dB for either low or high frequencies or both as threshold. When using 25 dB as threshold, the number of children with hearing impairment was 18 (10%). None of the children had hearing aids. Of 355 otoscopies available for evaluation, the majority were normal (n = 249, 70.1%). Perforation of the tympanic membrane was found in six ears (1.7%), of which all were unilateral. Other sequelae related to OM (i.e., circular atrophy and myringosclerosis) were found in 37 ears (10.4%). Children with OM-related otoscopy findings had significantly lower hearing tresholds compared to children without. Conclusion: A high prevalence of untreated hearing loss was found among examined school children in Sisimiut. Children with otoscopy findings indicating prior OM had significantly lower hearing tresholds compared to children without.